A Utilização de Exercícios de Técnica Pianística no Ensino e na Prática de Sete Professores de Piano do Recife. - Oliveira Filho, Manoel Theophilo Gaspar de (2015)
Historically, piano exercises have served a significant role in the development of piano pedagogy. Nonetheless, these drills still manage to provoke debates and cause frequent divergences of opinion among pianist and piano teachers world wide. Willing to offer further material for debate, the objective of this research is to develop a better understanding of how the teachers at the largest public schools in Recife (the Conservatório Pernambucano de Música and Universidade Federal de Pernambuco) handle the topic. In other words, whether or not they incorporate piano exercises into their teaching material. In order to collect this information, we used semi-structured interviews. As a theoretical basis of the proposed subject, this work will provide a historical description of piano technique and its evolution, explain the differences in approach of various “Piano Technique Schools”, explore the opinions of renowned pianists of the twentieth and twenty-first centuries, and compare those opinions to the ideologies of the teachers interviewed. The conclusion of this work relies on the fact that the use of technical exercises is still a controverse subject among piano teachers, surrounded by disagreements, conceptual incoherences and diversity of opinion.